Fuzzy logic controller implementation by using general purpose PIC microcontroller - Hanbay, Davut; Türko?lu, Ibrahim; Demir, Yakup (My University, 2005)
This paper presents an overview of fuzzy logic hardware. The Fuzzy Logic Controller (FLC) was designed for washing machine which is implemented on general purpose 8-bits PIC Microcontroller 16F877. The aim of this study is not only the implementation of FLC for washing machine but also the application of fuzzy logic controller for demonstration of basic principles in PC independent hardware applications. © 2005 IEEE.
Genel amaçli PIC-mikrodenetleyici kullanarak bulanik mantik denetleyici uygulamasi
IEEE 13th Signal Processing and Communications Applications Conference, SIU 2005 -- 16 May 2005 through 18 May 2005 -- Kayseri -- 69003
Keywords: Fuzzy sets; Logic design; Microcontrollers; Two term control systems; Washing machines; Fuzzy Logic Controller (FLC); Hardware applications; Programmable logic controllers